2021
DOI: 10.1038/s41392-021-00776-0
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of HBV-specific CD8+ T-cell responses by sequential low-dose IL-2 treatment in non-responder patients after IFN-α therapy

Abstract: Patients with chronic hepatitis B (CHB) undergoing interferon (IFN)-α-based therapies often exhibit a poor HBeAg serological response. Thus, there is an unmet need for new therapies aimed at CHB. This study comprised two clinical trials, including 130 CHB patients, who were treatment-naïve; in the first, 92 patients were systematically analyzed ex vivo for interleukin-2 receptor (IL-2R) expression and inhibitory molecules expression after receiving Peg-IFN-α-2b therapy. In our second clinical trial, 38 non-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 59 publications
1
39
0
2
Order By: Relevance
“…Human T cells can mature into αβT cells and γδT cells, and the signal strength of the TCR plays a critical role in lineage differentiation [ 23 ]. The quality and magnitude of CD8 + T-cell responses were important to overcome virus infections and kill tumour cells [ 24 ]. In addition, naïve CD4 + T cells could differentiate into effector Th cells that are characterized by the expression of distinct cytokines and transcription factors.…”
Section: Development and Subgroups Of Dntsmentioning
confidence: 99%
“…Human T cells can mature into αβT cells and γδT cells, and the signal strength of the TCR plays a critical role in lineage differentiation [ 23 ]. The quality and magnitude of CD8 + T-cell responses were important to overcome virus infections and kill tumour cells [ 24 ]. In addition, naïve CD4 + T cells could differentiate into effector Th cells that are characterized by the expression of distinct cytokines and transcription factors.…”
Section: Development and Subgroups Of Dntsmentioning
confidence: 99%
“…CD8+ T cells are important in tumor immunity, as they can clear tumors via multiple mechanisms ( 29 ). Numerous studies have shown that high infiltration of CD8+ T cells in the TIME is associated with good prognosis in many malignancies ( 30 , 31 ). In our study, we found that the CD8+ T effector signature was significantly upregulated in Subtype 2, which explains why Subtype 2 had a higher response and better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Freshly isolated PBMCs were resuspended and seeded in 24 well plates in RPMI 1640 medium (Gibco) supplemented with 10% fetal bovine serum (FBS, Gibco) and penicillin (100 U/mL)/streptomycin (100 μg/mL). Cells were stimulated with ionomycin (1μg/mL, Calbiochem) and phorbol 12-myristate 13-acetate (PMA) (50ng/mL, Sigma) or HLA-restricted CMV pp65 peptides ( key resources table ) in the presence of monensin (10μg/mL, Sigma) for 4hat 37°C and 5% CO 2 , as previously described ( Wang et al., 2021 ). Stimulated cells were collected and stained with monoclonal antibodies (mAbs, key resources table ) against CD45, CD3, CD56, and CD8, followed by permeabilization (eBioscience) for 20 min at 20°C, and then stained with mAbs ( key resources table ) against interferon-γ (IFN-γ) and tumor necrosis factor alpha (TNF-α) ( Wang et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%